Compromised gut–brain axis architecture in uremic encephalopathy: A case report with review of literature - Shanker, Varnit; Govil, Radhika; Shukla, Sanjay; Khandelwal, Mohit (Indian Journal of Case Reports, 2026)
Posterior reversible encephalopathy syndrome (PRES) is often clinically manifested by headaches, seizures, and altered sensorium, which coincide with clinical features of uremic encephalopathy (UE). Here, a case of a 12-year-old female with polycystic kidney and hepatic disease 1 positive polycystic chronic kidney disease (autosomal recessive polycystic kidney disease), presenting with non-specific abdominal pain, bloating, mouth ulcers, and vomiting, followed by status epilepticus, is reported. Magnetic resonance imaging of the brain showed features of atypical PRES. Gastrointestinal symptoms, UE, and PRES offer an interesting window into the common toxin-mediated damage to the gut–brain axis architecture. This report is followed by a crisp review of the literature.